JUSTIFIKASI HUKUM PADA AKTIVITAS KELOMPOK ARISAN PERSATUAN DI DESA PENIRAMAN KECAMATAN SUNGAI PINYUH KABUPATEN MEMPAWAH - Salsabila, Salsabila; Fahmi, Moch. Riza; Anggriana, Anggita (Al-Aqad, 2024)
The study aims to reveal Legal Justifications for the Get-Together Tradition Group Activities in Peniraman Village, Sungai Pinyuh District, Mempawah Regency. This research aims to find out: 1) The views of the people of Peniraman Village, Sungai Pinyuh District, Mempawah Regency regarding the tradition of the get-together group. 2) Justification of the law of the get-together tradition in Peniraman Village, Sungai Pinyuh District, Mempawah Regency. This research is a type of empirical normative research with a qualitative approach, while data collection techniques use primary data, namely observation, interviews, and documentation. Data collection tools used by the researcher are interview guides, paper stationery, and electronic devices. Meanwhile, data analysis techniques and concluding testing data validity use member-check. The results of the research show that: 1) The society of Peniraman Village considers the get-together group as a tradition that must be preserved because it contains positive things such as always maintaining friendly relations and the feeling of mutual help that is generated by the group tradition in Peniraman Village. 2) Because this group is well known by the public and does not conflict with the postulates of Sharia'. In terms of the validity of the get-together group, it is included in permissible transactions (permissible) to be carried out because there is an element of mutual help in it and there are no elements of usury or maisir that arise in the get-together group contract in Peniraman Village.